Melatonin and Its Effects on Plant Systems - Rahat Sharif; Chen Xie; Haiqiang Zhang; Marino B. Arnao; Muhammad Ali; Qasid Ali; Izhar Muhammad; Abdullah Shalmani; Muhammad Azher Nawaz; Peng Chen; Yuhong Li (Molecules, 2018)
Melatonin (N-acetyl-5-methoxytryptamine) is a nontoxic biological molecule produced in a pineal gland of animals and different tissues of plants. It is an important secondary messenger molecule, playing a vital role in coping with various abiotic and biotic stresses. Melatonin serves as an antioxidant in postharvest technology and enhances the postharvest life of fruits and vegetables. The application of exogenous melatonin alleviated reactive oxygen species and cell damage induced by abiotic and biotic stresses by means of repairing mitochondria. Additionally, the regulation of stress-specific genes and the activation of pathogenesis-related protein and antioxidant enzymes genes under biotic and abiotic stress makes it a more versatile molecule. Besides that, the crosstalk with other phytohormones makes inroads to utilize melatonin against non-testified stress conditions, such as viruses and nematodes. Furthermore, different strategies have been discussed to induce endogenous melatonin activity in order to sustain a plant system. Our review highlighted the diverse roles of melatonin in a plant system, which could be useful in enhancing the environmental friendly crop production and ensure food safety.